2010
DOI: 10.1186/1471-2199-11-102
|View full text |Cite
|
Sign up to set email alerts
|

A single hydrophobic cleft in the Escherichia coli processivity clamp is sufficient to support cell viability and DNA damage-induced mutagenesis in vivo

Abstract: BackgroundThe ubiquitous family of DnaN sliding processivity clamp proteins plays essential roles in DNA replication, DNA repair, and cell cycle progression, in part by managing the actions of the different proteins involved in these processes. Interactions of the homodimeric Escherichia coli β clamp with its known partners involves multiple surfaces, including a hydrophobic cleft located near the C-terminus of each clamp protomer.ResultsA mutant E. coli β clamp protein lacking a functional hydrophobic cleft (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Importantly, a single cleft on the clamp was sufficient to support this switch, and both the rim and cleft contacts were required (19). Taken together, these findings suggest that Pol IV must first contact the rim of the ␤ clamp immediately adjacent to the cleft that is bound by Pol III* prior to gaining access to the same cleft previously associated with the stalled Pol III* (19,45) (Fig. 1).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Importantly, a single cleft on the clamp was sufficient to support this switch, and both the rim and cleft contacts were required (19). Taken together, these findings suggest that Pol IV must first contact the rim of the ␤ clamp immediately adjacent to the cleft that is bound by Pol III* prior to gaining access to the same cleft previously associated with the stalled Pol III* (19,45) (Fig. 1).…”
mentioning
confidence: 54%
“…In addition to the cleft, Pols also contact noncleft surfaces (7,19,20,28,(42)(43)(44). These surfaces, together with a single cleft on the clamp, are sufficient for supporting viability of E. coli and managing the actions of its different Pols during UV-induced mutagenesis (45).…”
mentioning
confidence: 99%
“…As for Pol II, it was shown that the interaction of Pol IV with the b-clamp is essential to support its TLS activity in vivo (Becherel et al 2002). Until recently, it was thought that Pol III only contacts a single monomer of the dimeric b-clamp as shown in vitro (Sutton et al 2010). Together these observations appeared to comfort the so-called tool-belt model predicting simultaneous binding to the clamp of the replicative polymerase and a specialized polymerase (Pagès and Fuchs 2002;Indiani et al 2005).…”
Section: Rp Fuchs and S Fujiimentioning
confidence: 99%
“…We used nanoESI-MS under native conditions to assess whether sliding-clamp subunits from different species could form heterodimers with  Eco , with the rationale being that the dimerization interfaces would have to be chemically and structurally similar for formation of heterodimers, which would validate this interface as a broad-spectrum drug target. It is known that  Eco mutant subunits can be made to form heterodimers with the wild-type subunit (Scouten Ponticelli et al, 2009;Sutton et al, 2010;Jergic et al, 2013). Peaks in mass spectra corresponding to the m/z values of heterodimeric ions were observed for all pairwise combinations (Fig.…”
Section: Comparison Of Dimerization Interfacesmentioning
confidence: 89%